Theory of Time Asymmetry and Strangeness Oscillation of K° - Syros, C.; Ioannidis, G. S. (HNPS Advances in Nuclear Physics, 2019)
The predicted value for the T-asymmetry, AT eory, of the neutral kaons strangeness oscillation in the framework of the chronotopological stochastic quantum field theory is AT eory = 6 . 6 x l 0 - 3 and the corresponding diameter of the interaction proper-time neighborhood, is δ(τχ) = 2.382 χ IO- 2 7 s. The antiproton energy in the reaction for the kaon production is Ep = 200 MeV. The time evolution operator, C(TK), acting on the state vector gives two contributions, one unitary and one decoherent. AT eory as a function of Ep shows that Κ - decays (antimatter) were more abundant than matter decays at higher temperatures of the universe. C(TK) appears in two disjoint subsets of denumerably many forms, unitary and non-measure preserving. The evolution operator of the standard quantum field theory is identical to the zerothorder element of the unitary subset. The set of evolution paths Schronotop., produced by C(7A„) is denumerable (quantized) in contradistiction to the set, SFeynman, of trajectories in the path integral which is continuous. The value measured recently by the CPLEAR-Collaboration at CERN is A§xper·) = (6.6 ± 1.3) x 10"3 . The agreement with the predicted value is excellent.